Influence of Nonwoven Geotextiles and Geogrids on Shear Strength of Expansive Montmorillonite Clay - Assel Tulebekova; Zhanar Kusbergenova; Aliya Aldungarova; Gulshat Tleulenova; Dauren Yessentay; Uliya Abdikerova; Nargul Saktaganova; Atogali Jumabayev; Timoth Mkilima (Engineering Reports, 2025)
ABSTRACT Geosynthetic reinforcement plays a crucial role in stabilizing subgrade layers and enhancing the bearing capacity of soil in construction projects. Despite notable advancements in soil reinforcement techniques, there remains a lack of comprehensive understanding regarding the interactions between various geosynthetic materials and different soil types. This study investigates the effectiveness of different geosynthetic reinforcements in enhancing the shear strength of expansive montmorillonite clay. The research aims to compare the performance of two reinforcement types (biodegradable geocell and a nonwoven geotextile) against a conventional woven geogrid, assessing their influence on soil stability under various stress conditions. Reinforcing the expansive montmorillonite clay with either nonwoven geotextiles or geogrids effectively increased its shear strength under various normal stress levels. For example, at a normal stress of 100 kPa, geogrid reinforcement increased the shear strength from 50 kPa (unreinforced) to 65.5 kPa, while nonwoven geotextiles resulted in a shear strength of 51.2 kPa, highlighting the superior performance of geogrids in enhancing soil stability. Additionally, the use of nonwoven geotextile was found to enhance cohesion from 8 to 15 kPa. When exposed to moisture, the unreinforced soil expanded significantly, exhibiting a swelling strain of 12.8%. However, reinforcing the soil with biodegradable geocells (GC) substantially mitigated this expansion, reducing the swelling strain to 4.2%. While woven geogrids also limited swelling (7.5% strain), they were not as effective as the biodegradable geocells in minimizing volumetric changes.